Long‐Read Sequencing Resolves a Complex Structural Variant in PRKN Parkinson's Disease - Daida, Kensuke; Funayama, Manabu; Billingsley, Kimberley J.; Malik, Laksh; Miano‐Burkhardt, Abigail; Leonard, Hampton L.; Makarious, Mary B.; Iwaki, Hirotaka; Ding, Jinhui; Gibbs, J. Raphael; Ishiguro, Mayu; Yoshino, Hiroyo; et al. (Movement disorders, 2023)
Background Parkin RBR E3 ubiquitin‐protein ligase (PRKN) mutations are the most common cause of young onset and autosomal recessive Parkinson's disease (PD). PRKN is located in FRA6E, which is one of the common fragile sites in the human genome, making this region prone to structural variants. However, complex structural variants such as inversions of PRKN are seldom reported, suggesting that there are potentially unrevealed complex pathogenic PRKN structural variants. Objectives To identify complex structural variants in PRKN using long‐read sequencing. Methods We investigated the genetic cause of monozygotic twins presenting with a young onset dystonia‐parkinsonism using targeted sequencing, whole exome sequencing, multiple ligation probe amplification, and long‐read sequencing. We assessed the presence and frequency of complex inversions overlapping PRKN using whole‐genome sequencing data of Accelerating Medicines Partnership Parkinson's disease (AMP‐PD) and United Kingdom (UK)‐Biobank datasets. Results Multiple ligation probe amplification identified a heterozygous exon three deletion in PRKN and long‐read sequencing identified a large novel inversion spanning over 7 Mb, including a large part of the coding DNA sequence of PRKN. We could diagnose the affected subjects as compound heterozygous carriers of PRKN. We analyzed whole genome sequencing data of 43,538 participants of the UK‐Biobank and 4941 participants of the AMP‐PD datasets. Nine inversions in the UK‐Biobank and two in AMP PD were identified and were considered potentially damaging and likely to affect PRKN expression. Conclusions This is the first report describing a large 7 Mb inversion involving breakpoints outside of PRKN. This study highlights the importance of using long‐read sequencing for structural variant analysis in unresolved young‐onset PD cases. © 2023 The Authors. Movement Disorders published by Wiley Periodicals LLC on behalf of International Parkinson and Movement Disorder Society. This article has been contributed to by U.S. Government employees and their work is in the public domain in the USA. We investigated a family with early‐onset Parkinson’s Disease (PD). MLPA and short‐read sequencing confirmed a heterozygous PRKN deletion. Using long‐read sequencing, we identified a second variant in PRKN, a 7.4 Mbp inversion. Other genetically unresolved early‐onset PD cases may have complex structural variants which can be resolved using long‐read sequencing.